Transformation of Higher Education in Nepal: Emerging Challenges and the Necessity of Rethinking Approaches - Budhathoki, Drona; Upadhyay, Pradyumna (International Research Journal of MMC, 2026)
Education is a structured process that enables individuals to acquire the knowledge, skills, values, and attitudes necessary for personal development and meaningful contribution to society. It operates through formal institutions such as schools and universities as well as informal community-based learning environments, thereby empowering learners, strengthening citizenship, and promoting sustainable development and social inclusion. Higher education in Nepal faces several challenges, including outdated curricula, limited research capacity, inadequate infrastructure, and insufficient faculty development. The chief objective is to identify emerging challenges in Nepalese higher education and explore effective strategies for its improvement and transformation. An explanatory sequential mixed-methods research design was employed, involving purposive sampling of key stakeholders, including students, parents, and a pioneer academician. Data were collected through questionnaires, interviews, and document analysis in 2026, and they were examined using thematic analysis. The findings reveal weak governance, an outdated curriculum, limited research capacity, low student engagement, and inadequate scientific and practical education, along with employment-related challenges. These issues reflect structural, institutional, and pedagogical weaknesses that require coordinated reforms. The study emphasizes the need for policymakers and university administrators to implement need-based reforms in curriculum development, research enhancement, infrastructure improvement, and skilled human resource production. Strengthening these areas is essential for improving the quality and relevance of higher education in Nepal. The study is valuable for researchers and scholars by providing insights into existing challenges and supporting evidence-based policy formulation.